Fotografías, reseñas, comentarios y otros - Claro León, Jorge; Mejía, Francisco; Villaseñor, Jesús; Constantinides, Dinos; Luna Martínez, América; Vargas Longares, Amelia Araceli; García Gasca, Zujey; Reyes Palacio, Felipe; Arnulfo, Miguel Ángel; Solé Zapatero, Francisco Xavier; Bribiesca Sumano, María Elena; Padilla Medina, Rocío (Contribuciones desde Coatepec, 1997)
Fotografías, reseñas, comentarios y otros